(untitled) (Texas Journal of Medical Science, 2025)
Chronic hepatitis B (CHB) remains a major global public health concern. This review outlines current approaches to managing CHB in pregnant individuals. The rate of HBV infection in pregnancy generally mirrors that of the wider population in a given region. Universal screening for hepatitis B surface antigen (HBsAg) is essential during pregnancy. For those who test positive, further assessment may involve measuring hepatitis B e antigen, HBV DNA levels, alanine aminotransferase, and HBsAg quantitation. Clinical management is guided by the phase of HBV infection, which should ideally be established prior to conception. For individuals with CHB who may become pregnant, antiviral therapy serves two key purposes: to treat active liver disease and to prevent mother-to-child transmission. Tenofovir is the recommended antiviral agent during pregnancy for both indications. To prevent vertical transmission, every newborn to an HBsAg-positive mother should receive hepatitis B immunoglobulin and the first dose of hepatitis B vaccine within 12 hours of birth. Breastfeeding is not contraindicated for mothers with CHB.